Application and Development of Nano Material Technology in Archives Protection Technology. Issue 1 (2nd September 2022) - Sun, Rao; Zhou, Yang
Abstract: My country's archive protection technology has a long history, with a history of more than a thousand years. My country has a wide range of research on archive protection technology. The related research from historical and technical perspectives is very rich, and the advantages and disadvantages of previous archive protection technologies are integrated. Analysis and research on protection technologies that can be inherited and developed are still blank. At the same time, there are increasingly researches on nanomaterial technology. Based on this, this paper studies the application and development of nanomaterials in archive protection technology based on the unique properties of nanomaterials, and provides a reference for solving people's needs in the archive protection field, avoiding a lot of waste of manpower and material resources. In this paper, ZnO nanostructures with various morphologies were prepared by hydrothermal method and high temperature oxidation method. At the same time, ZnO nanomaterials and archive protection technology were combined to prepare nano-three-dimensional flower-like ZnO structure super-hydrophobic films. It shows that the application potential of nanomaterial technology in the field of archives protection is large, and it can be attached to the surface of archives to achieve antibacterial effect, and it can be better used in future archives protection work.